The Role of the Company in Generating Skills The Learning Effects of Work Organisation. Synthesis Report. CEDEFOP Document - European Centre for the Development of Vocational Training, Thessaloniki (Greece). (Luxembourg: Office for Official Publications of the European Communities, 1997)
This report synthesizes the findings of a study of continuing training policy in nine countries of the European Community: Belgium, Denmark, France, Germany, Italy, the Netherlands, Portugal, Spain, and the United Kingdom. The following are among the topics discussed: the study's objectives and methods; characteristics of new forms of work and production organization (diversity of forms of work organization and production models; quantitative versus qualitative flexibility; reliability and adaptability of production; reliability of interorganizational networks; flexibility, adaptability, and training of operators); principles behind new forms of work organization (problem of the newness of know-how; main lines in organizational restructuring, links to the dynamics of know-how and skills; restructuring of know-how: the Tandem product/market or the "marketable product"? know-how or attitudes; distancing: necessary conditions for the training content of new organizations, trends and connecter-trends); the increase in training and shifts in training efforts; discrete knowledge and discrete training; explicit training (varied use of formalized continuing training, policy design and content validation, recognition, and certification); and new training practices, training policy, and employment and labor relations policies (links between forms of training in enterprises and initial and continuing training policies, consequences for employment and the labor market, reversibility and irreversibility of new forms of organization, actors and the social dialogue). The bibliography contains 143 references. (MN)
Availability: Bernan Associates, 4611-F Assembly Drive, Lanham, MD 20706-4391; toll-free phone: 800-274-4447; e-mail: query@bernan.com; world wide web: http://www.bernan.com (catalogue no. HX-89-95-050-EN-C: 8 European Currency Units).
Electronic reproduction.
Available via the World Wide Web.
Keywords: Adult education; Communicative competence; Continuing education; Economic Change; Education Work Relationship; Educational Policy; Employer Employee Relationship; Employment Practices; Employment Qualifications; Foreign Countries; Job Skills; Job Training; Learning Processes; Organizational Change; Postsecondary Education; Public Policy; Skill Development; Synthesis; Training Methods; Vocational Education; Work Environment; Comparative Analysis; Reports, Research